Penerapan Pembelajaran Tematik Berbasis Kearifan Lokal melalui LKPD di SDN Jenggawah 01 Jember - Silfi Putri Suciyati; M. Suwignyo Prayogo; Naurana Nazla Syafa Kamilah; Azzarina Azka Humairoh (Advances In Education Journal, 2025)
This study aims to describe the application of local wisdom-based thematic learning through Student Worksheets (LKPD) at SDN Jenggawah 01 Jember. The background of this study stems from the importance of integrating local wisdom values into thematic learning in order to foster positive character and contextual understanding in students. The learning theme used is “Our Friendly Environment,” which is relevant to the social and cultural conditions of the Jenggawah community. This study used a descriptive narrative approach with a natural qualitative research design. Data were collected through observation, interviews, and documentation of fourth-grade teachers and students. The results showed that the application of LKPD based on local wisdom was able to increase student active involvement in the learning process, foster concern for the surrounding environment, and strengthen the values of mutual cooperation and responsibility. Teachers play an important role in integrating local values into thematic learning activities, both through the context of the material and practical field activities. This study confirms that the application of LKPD based on local wisdom not only strengthens conceptual understanding but also contributes to the character building of students in accordance with the Pancasila student profile.